Characterization of a novel species-specific 51-amino acid peptide, PEP51, as a caspase-3/7 activator in ovarian follicles of the ascidian, Ciona intestinalis Type A - Sakai, Tsubasa; Yamamoto, Tatsuya; Watanabe, Takehiro; Hozumi, Akiko; Shiraishi, Akira; Osugi, Tomohiro; Matsubara, Shin; Kawada, Tsuyoshi; Sasakura, Yasunori; Takahashi, Toshio; Satake, Honoo (Frontiers in Endocrinology, 2023)
Invertebrates lack hypothalamic-pituitary-gonadal axis, and have acquired species-specific regulatory systems for ovarian follicle development. Ascidians are marine invertebrates that are the phylogenetically closest living relatives to vertebrates, and we have thus far substantiated the molecular mechanisms underlying neuropeptidergic follicle development of the cosmopolitan species, Ciona intestinalis Type A. However, no ovarian factor has so far been identified in Ciona.In the present study, we identified a novel Ciona-specific peptide, termed PEP51, in the ovary. Immunohistochemical analysis demonstrated the specific expression of PEP51 in oocyteassociated accessory cells, test cells, of post-vitellogenic (stage III) follicles. Immunoelectron microscopy revealed that PEP51 was localized in the cytosol of test cells in early stage III follicles, which lack secretory granules. These results indicate that PEP51 acts as an intracellular factor within test cells rather than as a secretory peptide. Confocal laser microscopy verified that activation of caspase-3/7, the canonical apoptosis marker, was detected in most PEP51-positive test cells of early stage III. This colocalization of PEP51 and the apoptosis marker was consistent with immunoelectron microscopy observations demonstrating that a few normal (PEP51negative) test cells reside in the aggregates of PEP51-positive apoptotic test cells of early stage III follicles. Furthermore, transfection of the PEP51 gene into COS-7 cells and HEK293MSR cells resulted in activation of caspase-3/7, providing evidence that PEP51 induces apoptotic signaling. Collectively, these results showed the existence of species-specific ovarian peptidedriven cell metabolism in Ciona follicle development. Consistent with the phylogenetic position of Ciona as the closest sister group of vertebrates, the present study sheds new light on the molecular and functional diversity of the regulatory systems of follicle development in the Chordata.